Serum creatinine-to-albumin ratio as a prognostic marker for short- and long-term mortality in critically ill stroke patients: a MIMIC-IV study - Sun, Dong; Chen, Sichun; Bi, Ying; Wu, Shuang; Xie, Yu; Zhang, Renwei; Zhang, Lei; Dan, Bitang; Li, Huagang; Liu, Yang; Liu, Yumin; Mei, Bin; et al. (Frontiers in Neurology, 2025)
IntroductionStroke remains a leading cause of mortality and disability worldwide, with critically ill patients facing particularly poor outcomes. Existing prognostic markers often fail to capture the full spectrum of metabolic and nutritional disturbances in stroke. The serum creatinine-to-albumin ratio (sCAR), reflecting renal function and nutritional status, may offer improved mortality prediction for the intensive care unit (ICU)-admitted stroke patients.MethodsThis retrospective cohort study used the MIMIC-IV database (v2.2) to analyze 2,819 adult stroke patients admitted to the ICU. Patients were stratified into low- and high-sCAR groups based on an optimal cutoff of 0.419. Predictive performance was assessed using Cox regression, Kaplan–Meier survival analysis, and ROC and RCS curve modeling.ResultsPatients in the high sCAR group (≥0.419) demonstrated significantly higher short- and long-term mortality, including 28-day (31.7% vs. 16.7%, p < 0.001) and 1-year mortality (51.0% vs. 27.6%, p < 0.001). Multivariate Cox regression confirmed that elevated sCAR was independently associated with increased mortality risk at all endpoints, including 28-day (HR = 2.68, 95% CI: 2.28–3.14, p < 0.001) and 1-year (HR = 3.01, 95% CI: 2.61–3.47, p < 0.001). ROC analysis showed sCAR outperformed traditional markers, with an AUC of 0.618 for 28-day mortality and 0.639 for 1-year mortality. RCS curves revealed a non-linear association between sCAR and mortality risk, with thresholds indicating elevated risk for both short- and long-term outcomes.ConclusionThe sCAR is a powerful and clinically relevant biomarker for mortality prediction in critically ill stroke patients. By integrating renal and nutritional assessments, sCAR enhances early risk stratification and supports individualized ICU management.